Proposing a knowledge management solution for e-learning. (4th June 2010) - Anitha, D.
Knowledge Management (KM) is a crucial research area for managing an organisation's knowledge assets. Knowledge-driven organisations tend to improve their potential with KM solutions. This paper proposes a KM solution for acquiring best results from the e-learning systems of academic institutions. The proposed solution gives a detailed vision of the KM processes which converge with the e-learning domain. It also indicates the information technology related tools and techniques for implementing the processes. The paper declares the need of a KM solution in e-learning so as to improve the learning processes by knowledge sharing, discovery and reuse.